Monitoring oxytocin signaling in the brain: More than a love story - Inga D. Neumann (Comprehensive Psychoneuroendocrinology, 2023)
More than any other neuropeptide, oxytocin (OXT) is attracting the attention of neurobiologists, psychologists, psychiatrists, evolutionary biologists and even economists. It is often called a “love hormone” due to its many prosocial functions described in vertebrates including mammals and humans, especially its ability to support “bonding behaviour”. Oxytocin plays an important role in female reproduction, as it promotes labour during parturition, enables milk ejection in lactation and is essential for related reproductive behaviours. Therefore, it particularly attracts the interest of many female researchers. In this short narrative review I was invited to provide a personal overview on my scientific journey closely linked to my research on the brain OXT system and the adventures associated with starting my research career behind the Iron Curtain.